2011
DOI: 10.1007/s00256-011-1122-6
|View full text |Cite
|
Sign up to set email alerts
|

Hard arteries, weak bones

Abstract: Given the close association between bone and blood, it is not that surprising how the two common diseases of artery and bone, namely atherosclerosis and osteoporosis, may in part share a common pathogenesis. Although atherosclerosis and osteoporosis are both clearly more prevalent in later years, there is nonetheless increasing evidence of a bone-vascular connect independently linking osteoporosis with atherosclerosis beyond the occurrence of shared risk factors such as age, gender, smoking, lifestyle factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…This weak correlation between marrow fat and BMD would tend to point toward extraneous hormonal factors and other factors influencing marrow fat accumulation in the elderly rather than mesenchymal stem cell differentiation alone. The bone marrow cavity is composed of fat and hematopoietic tissue as well as a relatively small amount of trabecular bone and vascular channels (29, 30). Within the rigid confines of the surrounding bone, an increase in one component should be accompanied by a corresponding decrease in one or more of the other components.…”
Section: Discussionmentioning
confidence: 99%
“…This weak correlation between marrow fat and BMD would tend to point toward extraneous hormonal factors and other factors influencing marrow fat accumulation in the elderly rather than mesenchymal stem cell differentiation alone. The bone marrow cavity is composed of fat and hematopoietic tissue as well as a relatively small amount of trabecular bone and vascular channels (29, 30). Within the rigid confines of the surrounding bone, an increase in one component should be accompanied by a corresponding decrease in one or more of the other components.…”
Section: Discussionmentioning
confidence: 99%
“…Our elderly male and female subjects with spondylolisthesis were all shorter; this is probably because subjects with spondylolisthesis are more likely to have narrowed disc spaces [15]. Lifestyles, such as alcohol consumption and cigarette smoking, can affect bone health [42]. Others suggested that diabetes and atherosclerotic disease may be associated with degenerative spondylolisthesis [43].…”
Section: Discussionmentioning
confidence: 99%
“…100 Bone mineral metabolism was also negatively correlated with hypertension (p ¼ 0.003), hypercholesterolemia (p ¼ 0.01), and prior cardiovascular events, which is not surprising given the well-known association between osteoporosis and arteriosclerosis, particularly arterial calcification. 100,106…”
Section: Bone Marrow Metabolismmentioning
confidence: 99%